Rupture in Polycystic Kidney Disease Presented as Generalized Peritonitis with Severe Sepsis: A Rare Case Report - Muhammed Zahir; Hassan Al Muttairi; Surjya Prasad Upadhyay; Piyush N. Mallick (Case Reports in Urology)
Recurrent upper urinary tract (renal) infections have been reported to be frequent in patients with autosomal dominant polycystic kidney disease and often difficult to treat. Female preference and enteric organism predominance suggest that these renal infections are acquired to retrograde from the lower urinary tract. We encountered a rare case of bilateral polycystic kidneys with spontaneous intraperitoneal rupture of multiple infected renal cysts causing generalized peritonitis leading to severe sepsis with multiorgan failure. The patient is successfully managed with nephrectomy followed by prolonged supportive care in intensive care unit.